Phenomenon of Demikhov. In the 1st Moscow Medical Institute named after Sechenov (1956–1960). V.P.Demikhov's second business trip to Germany (May, 1959). "Organ transplantation: Is it possible?" (1959). - S. P. Glyantsev (Трансплантология (Москва), 2016)
.